Evaluation of the ultrasound test for estimating the depth of cracks in concrete - Tavares de Araújo Silva, Marcela; Aquino Rocha, Joaquin Humberto; Barreto Monteiro, Eliana Cristina; Pávoas, Yéda V.; Kohlman Rabbani, Emilia R. (Revista ALCONPAT, 2018)
The objective of this study is to evaluate the ultrasound test to estimate the depth of cracks in concrete, using a mathematical model from the literature, also to verify the depth with better results. Four concrete prisms were molded for each proposed crack depth (5 cm, 10 cm and 15 cm), simulated through zinc plates, placed during molding and removed before the concrete hardened. The results show that the test is sensitive to detect the presence of cracks in the concrete. The mathematical model used allowed to estimate the most depths of cracks; but the results are scattered and with a high margin of error for the depths of 5 cm and 15 cm, and for 10 cm presented better results.